Comparative genomic and phenotypic description of Escherichia ruysiae: a newly identified member of the gut microbiome of the domestic dog - Dione, Niokhor; Mlaga, Kodjovi D.; Liang, Siyi; Jospin, Guillaume; Marfori, Zara; Alvarado, Nancy; Scarsella, Elisa; Uttarwar, Ruchita; Ganz, Holly H. (Frontiers in Microbiology, 2025)
IntroductionEscherichia ruysiae is a newly identified species within the Escherichia genus, yet its presence in domestic animals remains largely unexamined. This study characterizes four isolates detected for the first time in the domestic dog (Canis lupus familiaris), focusing on their phenotypic and genomic features.MethodsWe used culturomic methods to isolate four E. ruysiae isolates that were initially identified as Escherichia coli using MALDI-TOF mass spectrometry. Whole-genome sequencing confirmed that the isolates belonged to E. ruysiae, not E. coli. Phenotypic characterization included enzymatic activity assays and antimicrobial susceptibility testing. Comparative genomic analyses were performed on these four isolates, along with 14 additional E. ruysiae and representative genomes from the five other Escherichia species in order to assess genetic diversity and functional gene distribution.Results and discussionAll strains exhibited similar enzymatic activities and resistance to clindamycin, erythromycin, and metronidazole. The pangenome analysis revealed that most missing gene orthologs are related to motility followed by metabolism, including synthetases, reductases, phosphatases, permeases, transferases, and epimerases, as well as structural genes like efflux pumps and transporters. Phylogroup typing using the ClermonTyping method identified two main groups within the E. ruysiae species, Clade III and IV. Typical virulence genes associated with E. coli are absent in these strains. The multiple approaches used in this study expand our understanding of the diverse aspects of the recently described species, E. ruysiae.